TRANSMISSION MODEL OF DENGUE FEVER IN CASE OF TANGERANG CITY WITH SEVERAL SIMULATIONS. - utomo, rukmono (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2025)
The aim of our research is constructing mathematics model SIR-SI transmission of dengue virus in case of Tangerang City consider vaccination, fumigation and treatment. Background of our research is because so many cases of dengue fever in Tangerang. We use method compartment model and creating differential equation system. The Result tells us that our mathematics model giving two equilibrium points. As the first, we call as disease free equilibrium point and the second is endemic equilibrium point (Simulation 1). We also success determining basic reproduction number and we analyze local-stability around those equilibrium points. Local stability around is asymptotic stable with =0.7863699062 < 1 and local stable around endemic equilibrium point is asymptotic stable with =3.045597501> 1. For simulation 2 with the parameter , and changed from 0,9 into 1 we get result that the number of infected human is decrease and the number of recovery is increase for free disease condition. In the disease condition of simulation 2, the result seems like same of free disease condition in simulation 2 but not too significantly for decrease the number of infected human and the number of increase recovery human.